(untitled) (Baghdad Science Journal, 2018)
Commercially pure titanium (cpTi) is widely used as dental implant material although it was found that titanium exhibited high modulus of elasticity and the lower corrosion tendency in oral environment. Niobium(Nb) was chosen for this study as an alternative to cpTi implant material due to its bioinert behavior and good elastic modulus and moderate cost in addition to corrosion resistance. This study was done to evaluate the effect of biomimetic coating on the surface properties of the commercially pure titanium and niobium implants by in vitro and in vivo experiments. The in vitro study was involved etching the samples of each material in HCl then soaking in 10M NaOH aqueous solution. These samples were then immersed in a 5 times concentrated simulated body fluid for 14 days. Scanning Electron Microscope, Energy Dispersive X-ray, and X-Ray Diffraction tests were done to analyze surface changes. The in vivo study was done by the implantation of screw-shaped implants (two from each material, uncoated and the other was biomimetically coated) in the tibias of New Zealand rabbits. After 2 and 4 weeks of healing period, 20 rabbits were sacrificed for each period. A removal torque was done for ten animals in each group, whereas the other ten were used for histological testing and histomorphometric analysis with optical microscope.The in vitro experiments showed that the use of 14 days immersion in a concentrated simulated body fluid produced a layer of calcium phosphate on metal surfaces. The removal torque values and new bone formation were increased significantly in Nb than Ti, in coated than uncoated screws, and in 4 weeks than 2 weeks healing periods. The Nb implants had better biomechanical and biological properties than the commercially pure titanium implants and can be used as an alternative dental implant.